2010
DOI: 10.1080/09712119.2010.10539517
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network versus Multiple Regression Analysis for Prediction of Lifetime Milk Production in Sahiwal Cattle

Abstract: Gandhi, R.S., Raja, T.V., Ruhil, A.P. and Kumar, A. 2010. Artificial neural network versus multiple regression analysis for prediction of lifetime milk production in Sahiwal cattle. J. Appl. Anim. Res., 38: 233-237. First lactation records (1493) of Sahiwal cows comprising of age at first calving, first lactation 305-d or less milk yield, first lactation length, first service period and first dry period were analyzed to predict the lifetime milk production using multiple regression analysis (MRAJ and artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
(4 reference statements)
0
13
0
2
Order By: Relevance
“…However, the number of the use of ANNs is still few in animal science (and a number of other fields). This limited use of ANN in animal science is paradoxical as data analyses are often done in this field despite that a few studies [3], etc. have shown ANNs to be more powerful than most traditional statistical prediction methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of the use of ANNs is still few in animal science (and a number of other fields). This limited use of ANN in animal science is paradoxical as data analyses are often done in this field despite that a few studies [3], etc. have shown ANNs to be more powerful than most traditional statistical prediction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it has potential as an alternative to the MLR model in different breeds 17,[22][23][24] . Gandhi et al 17,18 have developed the optimum equation incorporating three variables, namely age at first calving (AFC), FL305DMY and first lactation length (FLL). They found the ANN was more accurate than MLR for prediction of LTMY on the basis of early lactation traits in Sahiwal cattle.…”
mentioning
confidence: 99%
“…[4][5][6]8,[16][17][18][19] . Some studies showed that prediction of milk yield by using ANN model was more accurate than Wood's model 16,20 as well as by the MLR method [17][18][19]21 . Hence it has potential as an alternative to the MLR model in different breeds 17,[22][23][24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MLP uses the back propagation learning algorithm, which aims to specify the best parameters to model the relationship between the input and output variables [ 14 ]. ANNs, among other data mining techniques, combined with spectral data, have been increasingly used in animal science (i.e., for the detection of mastitis, determination of culling reasons, prediction of milk yield during lactation) [ 15 , 16 ]. Nonetheless, the application of these methods to predict collagen and IMCT properties has, as far as we know, not been addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%